Razlika med zgodnjo in pozno obravnavo otrok z motnjo avtističnega spektra - Zakrajšek, Petra (Anthropos (Ljubljana), 2025)
This systematic literature review examines the association between the timing of diagnosis and intervention and developmen- tal outcomes in children with autism spectrum disorder. The aim of this review was to synthesize and describe outcomes associated with early diagnosis and intervention, as well as those associated with later diagnosis and intervention. The review included 11 studies written in English that compared the effects of early and late diagnosis and inves- tigated the effectiveness of various interventions for autism spectrum disorder. The review utilized three databases (PubMed, ScienceDirect and Web of Science), focusing on research published between 2020 and 2024. The quality of the selected studies was assessed using standardized checklists from the Critical Appraisal Skills Programme (casp) and the Joanna Briggs Institute (jbi). The results indicate that early diagnosis and intervention significantly improve social, cognitive, motor, emotional development, and the development of behavioural characteristics in children with autism spectrum disorder. Children who received early intervention showed better results in social communication, adaptive behaviour, cognitive abilities, fine motor skills, and language proficiency. In contrast, late diagnosis is often associated with more severe symptoms and greater developmental delays. A key finding is that early intervention and diagnosis are crucial for reducing autism spectrum disorder symptoms and improving the quality of life for affected children, while late diagnosis can lead to long-term negative consequences. The review highlights the importance of timely intervention for the optimal development in children with autism spectrum disorder and suggests directions for future research focused on the long-term effects of various interventions.
Keywords: autism spectrum disorder; child development; early diagnosis; early intervention; late diagnosis; late intervention; motnja avtističnega spektra; pozna diagnoza; pozna intervencija; razvoj otroka; zgodnja diagnoza; zgodnja intervencija